Analisis Harga Pokok Penjualan dan Laba Kontribusi terhadap Volume Penjualan pada Perum Bulog Divre Sumut - Safitri Sembiring, Anggi; laila, Nur; Wahyuni Lubis, Arnida (ILTIZAM Journal of Shariah Economics Research, 2023)
This study aims to determine the cost of rice sold in increasing sales volume and how the profit contribution of Perum BULOG Divre Sumut on rice sales to sales volume. This research method is qualitative research. The results of data analysis in this study indicate that the sales volume of rice at Perum BULOG Divre Sumut continues to increase. Even though in 2022 the cost of goods sold will increase compared to the previous year, this will not have a negative impact on sales volume. Furthermore, the results of the calculation of contribution profit can also be seen that the sale of rice which generates the highest contribution profit as the largest contributor to profit for the company is in 2020, namely by obtaining a contribution profit ratio of 59.50% so by analyzing HPP and contribution profit to the company’s sales volume that from the HPP which can increase revenue at the North Sumatra Regional Bureau of Logistics Perum BULOG so that the North Sumatra Regional Division of Regional Logistics Perum BULOG. From the results of data analysis, a break even point (BEP) value of IDR 55,629,728 or 1,220 tons was obtained. Under these circumstances, the company will not suffer losses but also will not make a profit. Whereas for 2023, the company has set a profit target of 30% of its total sales, so the company must be able to sell its rice products of IDR 16,733,601,071.